POVERTY REDUCTION THROUGH STRENGTHENING THE ROLE OF COOPERATIVE INSTITUTIONS: CASE STUDY OF RURAL RICE FARMING COMMUNITIES - Ridwan, Mochamad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
This study aims to reveal the actual role of rural cooperative institutions in reducing poverty through improving the performance of farming communities, especially rice farmers in rural areas. This study is a case study conducted in Sri Kuncoro Village, Pondok Kelapa District, Bengkulu Tengah Regency (as the selected research sample location). Data were collected through the interview, observation, focus group discussion, and documentation methods. Sampling was done by the purposive sampling method. The data collected were analyzed by qualitative (descriptive) and quantitative methods. The results showed that through quantitative analysis it was found that the depth (P1) and severity (P2) indexes of poverty in rural rice farming communities were P1 = 0.023 and P2 = 0.004 (both in the low category). Through qualitative analysis, it is revealed that the role of cooperative institutions in rural areas is still low, which has implications for weak efforts to reduce poverty in rice farming communities (as evidenced by the decrease in the depth and severity indexes of poverty which has not reached the expected level).